Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/plb.12189
|View full text |Cite
|
Sign up to set email alerts
|

Differences in female reproductive success between female and hermaphrodite individuals in the subdioecious shrub Eurya japonica (Theaceae)

Abstract: Subdioecy is thought to occupy a transitional position in the gynodioecy-dioecy pathway, explaining one of the evolutionary routes from hermaphroditism to dioecy. Quantifying any female reproductive advantage of females versus hermaphrodites is fundamental to examining the spectrum between subdioecy and dioecy; however, this is challenging, as multiple interacting factors, such as pollen limitation and resource availability, affect plant reproduction. We compared the female reproductive success of females and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Previous work showed that trioecy (subdiocy) can be maintained under pollen limitation of female seed production because pollen limitation reduces the fitness of females but not self-fertile hermaphrodites, counteracting the seed fertility advantage of females in subdioecious population (Maurice and Fleming 1995; Fleming et al 1998; Wolf and Takebayashi 2004). However, in self-incompatible E. japonica , considering the weakened reproductive advantage of females against hermaphrodites under natural conditions (Wang et al 2015), although E. japonica is transitioning toward dioecy, pollinator-mediated pollen limitation may suppress enhanced fertility of females and males, thereby promoting the persistence of hermaphrodites in this E. japonica population (i.e. stable subdioecy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work showed that trioecy (subdiocy) can be maintained under pollen limitation of female seed production because pollen limitation reduces the fitness of females but not self-fertile hermaphrodites, counteracting the seed fertility advantage of females in subdioecious population (Maurice and Fleming 1995; Fleming et al 1998; Wolf and Takebayashi 2004). However, in self-incompatible E. japonica , considering the weakened reproductive advantage of females against hermaphrodites under natural conditions (Wang et al 2015), although E. japonica is transitioning toward dioecy, pollinator-mediated pollen limitation may suppress enhanced fertility of females and males, thereby promoting the persistence of hermaphrodites in this E. japonica population (i.e. stable subdioecy).…”
Section: Discussionmentioning
confidence: 99%
“…Hand-pollination treatments also revealed that seeds sired with pollen from male individuals exhibited better performance. Given that the female reproductive success of female individuals is higher than that of hermaphrodites and that hermaphrodites are self-incompatible in E. japonica (Wang et al 2015), pollen limitation may inhibit the shift and permit the persistence of hermaphrodites in this E. japonica population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is inconsistent with our previous results that male individuals have an advantage in male fertility over hermaphrodites in hand‐pollinated crosses (Wang, Matsushita, Tomaru, & Nakagawa, 2016). Considering the weakened reproductive success of females versus hermaphrodites under natural conditions in this  E. japonica population (Wang et al., 2015), pollinator‐mediated interaction and reproductive success through male and female functions may be related to the gradual change in the sex ratio of E. japonica .…”
Section: Discussionmentioning
confidence: 99%
“…; for details of the study site, see Wang, Matsushita, Tomaru, & Nakagawa, 2015). Plot 1 was destroyed for construction of a building in May 2012, and we added one plot (Plot 4, 20 × 20 m) at the Higashiyama Zoo and Botanical Gardens, Nagoya, Japan (35°09′N, 136°58′E, 79–86 m a.s.l.)…”
Section: Methodsmentioning
confidence: 99%